TPH2 5′- and 3′-Regulatory Polymorphisms Are Differentially Associated with HPA Axis Function and Self-Injurious Behavior in Rhesus Monkeys - Chen, Guo-Lin (2010)
Tryptophan hydroxylase-2 (TPH2) synthesizes neuronal serotonin and is linked to numerous behavioral traits. We have previously characterized the functionality of polymorphisms (especially 2051A>C) in 3′-UTR of rhesus monkey TPH2 (rhTPH2). This study further assessed the functionality of additional polymorphisms (−1605T>C, −1491Tn, −1485(AT)n, −1454A>G, −1325In>Del and −363T>G) in rhTPH2 5′-FR, and evaluated the effects of rhTPH2 5′ and 3′ genotypes on central serotonin turnover, hypothalamic-pituitary-adrenal (HPA) axis function and self-injurious behavior in 32 unrelated adult male monkeys of Indian origin. Haplotypes of the rhTPH2 5′-FR polymorphisms exert a significant, cell-dependent effect on reporter gene expression, primarily conferred by −1485(AT)n. The −1485(AT)n and 2051A>C polymorphisms interact to influence CSF 5-HIAA and plasma ACTH in the afternoon. While −1485(AT)n exerts significant main effects on the afternoon cortisol level and nocturnal HPA negative feedback, 2051A>C has significant main effects on the morning cortisol level and cortisol response to ACTH challenge, as well as marginally significant main effects on the daytime HPA negative feedback and self-biting rate. In addition, the genotype/allele frequency of the 5′-FR-1325Ins>Del differed significantly between the self-wounders and non-wounders, whereas 3′-UTR 2128S>L polymorphism differed significantly in genotype/allele frequency between the high- and low-frequency biters. This study demonstrates the functionality of rhTPH2 5′-FR polymorphisms, and provides evidence for the differential association of rhTPH2 5′-FR and 3′-UTR polymorphisms with HPA axis function and SIB. Our findings shed light on the role of TPH2 gene variance in physiology and behavioral traits, and also contribute to the understanding of the pathophysiology and genetics of SIB.